2022
DOI: 10.3389/fendo.2022.865863
|View full text |Cite
|
Sign up to set email alerts
|

Residual Risk of Coronary Atherosclerotic Heart Disease and Severity of Coronary Atherosclerosis Assessed by ApoB and LDL-C in Participants With Statin Treatment: A Retrospective Cohort Study

Abstract: BackgroundLow-density lipoprotein cholesterol (LDL-C) is the primary target of lipid-lowering therapy on the management of hypercholesterolemia in the United States and European guidelines, while apolipoprotein B (apoB) is the secondary target. The objective was to determine if elevated levels of apoB is superior to LDL-C in assessing residual risk of coronary atherosclerotic heart disease and severity of coronary atherosclerosis in participants with statin treatment.MethodsThis study included 131 participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…However, there was no association between the progression risk and elevated LDL-C levels while receiving statins therapy, which was in line with a previous study conducted by Yao et al [ 31 ]. They concluded that higher apoB levels, rather than LDL-C levels were significantly correlated with new-onset CAD in participants who received statins therapy.…”
Section: Discussionsupporting
confidence: 91%
“…However, there was no association between the progression risk and elevated LDL-C levels while receiving statins therapy, which was in line with a previous study conducted by Yao et al [ 31 ]. They concluded that higher apoB levels, rather than LDL-C levels were significantly correlated with new-onset CAD in participants who received statins therapy.…”
Section: Discussionsupporting
confidence: 91%
“…Apo B is a key structural protein component of all major atherosclerotic lipoproteins (LDL-C, VLDL-C, IDL-C, and Lp [a]). [ 3 ] It has been shown to be a better predictor of ASCVD than LDL-C. [ 19 , 20 ] The Apo B/A1 ratio is also a good predictor of ASCVD. The Apo A1 is an anti-atherosclerotic lipoprotein and the main apolipoprotein incorporated into HDL-C.…”
Section: Discussionmentioning
confidence: 99%
“…[17,18] However, biomarkers ). [3] It has been shown to be a better predictor of ASCVD than LDL-C. [19,20] The Apo B/A1 ratio is also a good predictor of ASCVD. The Apo A1 is an anti-atherosclerotic lipoprotein and the main apolipoprotein incorporated into HDL-C.…”
Section: Discussionmentioning
confidence: 99%
“…ApoB/ApoA1 and GDF-15 may be helpful for predicting the occurrence of CAD in patients with T2DM. Yao T, 2022 41 Not mentioned Cohort Coronary atherosclerotic heart disease To determine if elevated levels of apoB is superior to LDL-C in assessing residual risk of coronary atherosclerotic heart disease and severity of coronary atherosclerosis in participants with statin treatment. NA 131 Elevated apoB are superior in assessing the residual risk of coronary atherosclerotic heart disease and severity of coronary atherosclerosis in participants with statin treatment.…”
Section: Introductionmentioning
confidence: 99%